PENGEMBANGAN VIDEO INTERAKTIF SAINS UNTUK MENINGKATKAN PERKEMBANGAN KOGNITIF ANAK USIA 5-6 TAHUN DI TAMAN KANAK KANAK HARAPAN KAMI KETINGGIAN - Yosi Isratati; Delfi Eliza (Jurnal Educhild : Pendidikan dan Sosial, 2022)
This study aims to develop interactive science videos to improve early childhood cognitive development. The method used is Research and Development (R&D) with a 4-D model. This research was conducted in Harapan Kami Ketinggian Kindergarten. In this study, the stages of validation, practicality and effectiveness were carried out. The results of the validity test obtained an average of 86.22% while the practicality test of the teacher's response reached 92.18℅ and 94.43℅ for the observation of children's learning, testing the effectiveness of learning activities reached 95.41℅ and the effectiveness of children's learning outcomes 87.35℅. Based on these results, the developed science interactive video media can be used and practically applied in Kindergarten.